The New Normal of Fishery Agribusiness: Study on The Strategy Of Recovery of Aquaculture during Covid-19 Emergency in Magelang - Rochvita, Ana; Permadi, Jefri (Agrikan Jurnal Agribisnis Perikanan, 2021)
The Covid-19 is known to be affected to the aquaculturist in Magelang. This sector takes second main in supporting the community's economy. Therefore, the Aquaculture is needed to be recovered after the Covid-19. The aims of the research to determine the recovery strategy of aquaculture during the Covid-19 to the new normal. Questionnaires, interviews and field observations was used for data collection. The people were choosed as the respondents by purposive method. Respondent criteria were taken based on location, duration of aquaculture and type of aquaculture. Data were analyzed using SWOT. The identification of internal and external factors are used to determine the strength-weak and opportunity-treat in SWOT analysis. The results of the SWOT analysis obtained various strategies for the recovery of aquaculture businesses during the Covid-19 pandemic to the new normal, including: increasing production capacity, digitizing aquaculture businesses, increasing the frequency of mentoring and group development by the government, improving product quality, business diversification, proportionality of the number cultivators in the hatchery and rearing segment, providing education to farmers regarding the impact of Covid-19, strengthening capital, expanding the implementation of the Independent Fish Feed Movement program, protecting the farmers, and strengthening of market access.